FOTOSSENSOR AMPEROMÉTRICO À BASE DE LARANJA DE ACRIDINA/TiO2 PARA A DETERMINAÇÃO DE ÁCIDO CLOROGÊNICO EM AMOSTRAS DE ALIMENTOS. - SOUSA, Kelline Alaide Pereira (2018)
The present work is based on the development of a highly selective photoelectrochemical sensor for the determination of chlorogenic acid (CGA), a phenolic antioxidant, using a indium doped tin oxide electrode (ITO) modified with titanium dioxide (TiO 2 ) and acridine orange (AO). A light emitting diode (LED) lamp was used as the source of irradiation for the photoelectrochemical system. The materials that compose the photosensor were individually and simultaneously characterized by Fourier transform infrared spectroscopy (FTIR) and electrochemical impedance spectroscopy (EIS). The developed photosensor was named ITO/LA/TiO 2 and showed a rapid response to the analyte with high photocurrent for the CGA when compared to the ITO/LA and ITO/TiO2 sensors. Under optimized experimental and operational conditions, the ITO/LA/TiO 2 based sensor showed a linear correlation between the photocurrent and the CGA concentration in a concentration range of 2 to 200 μmol L -1 , as well as a detection limit of 0.54 μmol L -1 . The sensor was applied for the determination of CGA in soluble coffee, tea and apple juice samples by using the standard addition method. The accuracy of the sensor was evaluated through addition and recovery studies of the analyte providing recovery percentages from 102.16% to 102.42%. The accuracy of the sensor was verified by evaluating the repeatability of the measurements for several prepared sensors, providing a relative standard deviation (RSD) lower than 2 % indicating an excellent result for the proposed sensor. The selectivity of the sensor was tested by evaluating different species commonly found in samples containing the CGA and the results obtained suggest that there is no significant interference of these compounds on the analyte response, demonstrating a good selectivity for the photoelectrochemical sensor. The photosensor showed to be an efficient method for the determination of the CGA antioxidant in food samples, in a practical, fast, high reliability and low cost.